Sexual assault as a risk factor for gynaecological morbidity: An exploratory systematic review and meta-analysis - Hassam, Tayla; Kelso, Emma; Chowdary, Prathima; Yisma, Engida; Mol, Ben W.; Han, Alice (European journal of obstetrics & gynecology and reproductive biology, 2020)
Among Australian females, sexual assault affects 1 in 5 Australian women [1], and 1 in 10 girls [2]. While it is well known that females who experience sexual assault have an increased risk of future pelvic pain, there is limited knowledge regarding the occurrence of other gynaecological morbidity. We performed systematic review and meta-analysis for the relationship between sexual assault and gynaecological morbidity. We searched online electronic databases for observational studies on the subject published between 1993 and 2018. Search terms included variants of ‘sexual abuse’, ‘sexual assault’ and a range of gynaecological morbidity. Two independent reviewers completed study selection, quality assessment and data extraction. For each gynaecological symptom we calculated common odds ratios and 95 % confidence intervals in relation to sexual abuse history. Our search identified 1846 studies, of which 38 studies were included. A history of sexual assault was significantly associated with overall gynaecological morbidity (RR 1.42; 95%CI, 1.27–1.59), pelvic pain (RR 1.60; 95%CI, 1.36–1.89), ‘dyspareunia’ (pooled RR 1.74, 95%CI, 1.50–2.02); ‘dysmenorrhea’ (pooled RR 1.20; 95%CI, 1.11–1.29); ‘abnormal menstrual bleeding’ (pooled RR 1.29; 95%CI, 1.12–1.49)) and ‘urinary incontinence’ (pooled RR 1.31; 95%CI, 1.12–1.53)), while association was not statistically significant for ‘vaginismus’(pooled RR 1.71; 95%CI, 0.87–3.36) and ‘vulvodynia’ (pooled RR 1.49; 95%CI, 0.76–2.91). There was no relation with ‘prolapse’ (pooled RR 1.10; 95%CI, 0.53–2.30). Females with a history of sexual assault have a significantly increased risk of different gynaecological disorders later in life.